Microfinance in the Philippine setting: A comparative assessment of the operational and financial efficiency of the People's Credit and Finance Corporation (PCFC) and Tulay sa Pag-Unlad Inc. (TSPI) - Antonio, Michael G. (Animo Repository, 2004)
This paper centers on the comparative assessment of the operational and financial efficiency of the People’s Credit and Finance Corporation (PCFC) and Tulay Sa Pag-Unlad Inc.(TSPI). This study examines how the two microfinance institutions – the PCFC as a government controlled entity involved in wholesale microfinance lending while the TSPI is engaged in microfinance retail lending performed their business operations and incorporates an assessment of their financial standing for the period 1998 to 2001. Parameters were established as a tool of assessing said institutions’ efficiency in the delivery of adequate and responsive microfinance services and were based on variables and components of sustainable microfinance practices formulated by the technical working group headed by the National Credit Council and Coalition of Microfinance. Concepts of sustainable microfinance services were then operationalized through the application of the Balanced Scorecard Approach. The potential of microfinance as a development instrument has not yet been fully realized as such the study intends to outline and analyze the intricacies involved in the operations of microfinance institutions amidst the prevailing policy environment as well as other pertinent issues and concerns that may have a direct or indirect impact in the conduct of their operations.